Utilization of Social Media Instagram as The Formation of Brand Awareness on Cv. Sinaro - Widiarrachman, R. Fajar (Media Wisata, 2024)
The use of Instagram social media as a promotional tool is no longer a strange thing for a company, especially for companies operating in the field of consulting services which aim to provide information related to the services offered so that they can increase brand recognition to customers. What you want to achieve is to find out the use of Instagram social media as a form of brand awareness on CVs. Sinaro. The methods used in this research are qualitative descriptive as well as interviews and observation which are used as techniques for collecting data. The research results show that the CV.Sinaro company has not utilized the use of Instagram social media to create brand awareness for the company. So researchers recommend to companies to create Instagram as an effort to form brand awareness for the CV.Sinaro company by paying attention to the 5 main components in maximizing the use of Instagram as a promotional media according to Politwika (2015), namely creating an Instagram profile, business logo, description on the profile, uploading photos/videos , and hashtags.